A validation study of the Persian version of McKenzie's multiple intelligences inventory to measure profiles of pre-university students - Hajhashemi, Karim; Wong, Bee Eng (Universiti Putra Malaysia Press, 2010)
Traditionally, intelligence was viewed as a single static entity. Revolutionizing the once-dominated "singlestatic entity" conceptualization, Gardner initially (1983) proposed his theory of Multiple intelligences (MI) that encompasses seven different areas of intelligence (verbal-linguistic, logical-mathematical, musical-rhythmic, visual-spatial, bodily-kinesthetic, interpersonal, and intrapersonal), and later on added the eighth and ninth areas (naturalist and existential) in 1999. Based on the theory of Multiple Intelligences (MI), a person may be viewed as intelligent in any of these areas, and the identification of the dominant intelligence type has proven to have pedagogic implications. McKenzie's MI questionnaire (1999) is one of the established tools to identify the typology of intelligence. The present study aims to validate the Persian version of the MI Inventory (questionnaire) proposed by McKenzie (1999). This instrument provides an objective measure of MI. This paper describes the validation exercise of the abovementioned questionnaire that involved 173 pre-university students of both genders in Tehran. In addition, the variables gender and discipline were also considered in this study. The findings of the study indicate that overall, the Persian version of the questionnaire has a high reliability. In addition, the results show a moderate to high relationship between gender and MI profiles of the students.